Reactive gliosis and neuroinflammation: prime suspects in the pathophysiology of post-acute neuroCOVID-19 syndrome - Saucier, Jacob; Comeau, Dominique; Robichaud, Gilles A.; Chamard-Witkowski, Ludivine (Frontiers in Neurology, 2023)
Introduction: As the repercussions from the COVID-19 pandemic continue to unfold, an everexpanding body of evidence suggests that infection also elicits pathophysiological manifestations within the central nervous system (CNS), known as Neurological symptoms of Post-Acute Sequelae of COVID infection (NeuroPASC). Although the neurological impairment and repercussions associated NeuroPASC have been well described in the literature, its etiology remain to be fully characterized.Objectives: This mini review explores the current literature, which elucidates various mechanisms underlining NeuroPASC, its players, and regulators leading to persistent neuroinflammation of affected individuals. Specifically, we provide some insight on the various role played by microglial and astroglial cell reactivity in NeuroPASC, and how these cell subsets potentially contribute to neurological impairment in response to direct or indirect mechanisms of CNS injury.Discussion: A better understanding of the mechanisms and biomarkers associated with this maladaptive neuroimmune response will thus provide better diagnostic strategies for NeuroPASC and reveal new potential mechanisms for therapeutic intervention. Altogether, the elucidation of NeuroPASC pathogenesis will improve patient outcome and mitigate the socioeconomical burden of this syndrome.